AMF species do matter: Rhizophagus irregularis and Funneliformis mosseae affect healthy and PVY-infected Solanum tuberosum L. in a different way - Deja-Sikora, Edyta; Werner, Klaudia; Hrynkiewicz, Katarzyna (Frontiers in Microbiology, 2023)
In this study we examined the effect of two AMF species, Rhizophagus irregularis and Funneliformis mosseae on growth parameters, oxidative stress indicators and photosynthetic capacity of Solanum tuberosum L. infected with potato virus Y (PVY). We found that two AMF species colonized plant roots to varying degree (ca. 38% for R. irregularis vs. 20% for F. mosseae). R. irregularis had more positive effect on potato growth parameters, causing significant increase in total fresh and dry weight of tubers, also in virus-infected plants. Furthermore, this species lowered hydrogen peroxide level in PVY-positive leaves and positively modulated levels of non-enzymatic antioxidants, i.e. ascorbate and glutathione in leaves and roots. Finally, both endomycorrhizal fungi contributed to reduced lipid peroxidation and alleviation of virus-induced oxidative damages in plant tissues. We also confirmed indirect interaction between AMF and PVY inhabiting the same host. Two AMF species seemed to have different ability to colonize roots of virus-infected host, as R. irregularis showed stronger drop in mycorrhiza development in presence of PVY. At the same time we noticed that endomycorrhiza exerted the effect on virus multiplication, causing increased PVY accumulation in plant leaves and decreased concentration of virus in roots. Concluding, the effect of AMF-plant interaction may differ depending on genotypes of both symbiotic partners. Additionally, indirect AMF-PVY interaction takes place in host plant, which results in diminished development of endomycorrhiza and changed distribution of viral particles in plant tissues.